2004
DOI: 10.21236/ada426334
|View full text |Cite
|
Sign up to set email alerts
|

Apache Aviator Visual Experiences With the IHADSS Helmet-Mounted Display in Operation Iraqi Freedom

Abstract: I i"'*fl|Hi1.jii-Ho if *WtJ'/ Approved for public release, distribution unlimited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 7 publications
1
9
0
Order By: Relevance
“…Recognizing the shift in the role of the AH-64 attack helicopter, the study concluded with a recommendation for a future investigation that would encompass AH-64 pilots operating in the urban combat environment. 9 This recommendation was pursued by Heinecke et al, 10 who repeated a variant of the OIF Study in 2006. This study again found reduced frequencies of reports of visual complaints, consistent with the 2003 OIF study.…”
Section: Figure 11 Cohort Study Logomentioning
confidence: 99%
See 1 more Smart Citation
“…Recognizing the shift in the role of the AH-64 attack helicopter, the study concluded with a recommendation for a future investigation that would encompass AH-64 pilots operating in the urban combat environment. 9 This recommendation was pursued by Heinecke et al, 10 who repeated a variant of the OIF Study in 2006. This study again found reduced frequencies of reports of visual complaints, consistent with the 2003 OIF study.…”
Section: Figure 11 Cohort Study Logomentioning
confidence: 99%
“…The period post-9/11 allowed for studies during actual combat operations to determine if peacetime training and combat flight environments differed. [9][10] In this current report, the authors have reviewed the extant literature and provide a summary of the seminal studies investigating visual performance and perception issues performed over the past three decades.…”
Section: Introductionmentioning
confidence: 99%
“…By mounting the IHADSS behind the tinted visor, Apache aviators are capable of flying daylight missions with HMD symbology. 1,2 Mounting the HMD combiner lens outside of the visor's position will have performance issues (e.g., center of mass, image contrast, etc.) that need to be understood, and engineering solutions must be sought to overcome these performance losses.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies [1][2][3][4][5] have documented pilot reports of degraded visual cues, visual symptoms, and visual illusions while flying using the Integrated Helmet and Display Sighting System (IHADSS) monocular helmet-mounted display (HMD) fielded on the AH-64 Apache helicopter. Prior to 2003, all of these studies were conducted in relatively benign environments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The most recent study, conducted in late 2003 during Operation Iraqi Freedom (OIF), was the first to investigate the presence of visual complaints and artifacts in an operational combat environment. 5 The study consisted of two parts, a written questionnaire and an oral interview. A previous paper presented the results of the questionnaires, which documented a lower reporting rate for most visual illusions and complaints.…”
Section: Introductionmentioning
confidence: 99%